POST-WITHDRAWAL LEGAL IMPLICATIONS OF INTERNATIONAL AGREEMENTS CONCLUDED WITHIN THE FRAMEWORK OF THE EU LEGAL ORDER FOR THE WITHDRAWING MEMBER STATE - Mustafa T. Karayiğit (Ankara Avrupa Çalışmaları Dergisi, 2020)
The article examines post-withdrawal legal implications of EU only/pure and mixed agreements for the withdrawing Member State, in particular the UK, as a contracting party and/or a successor of the EU. It underlines the complexity of the legal implications of those agreements on the basis of the nature of vertical delimitation of competences. It draws attention not only to the nature of EU competences and the agreements with their purpose, object, context and wording, but also to third contracting parties’ positions (consent, refusal or dialogue etc. towards continuity or replacement of existing agreements) for the post withdrawal real legal effects of such agreements.